PANCASILA SEBAGAI LANDASAN HUKUM DI INDONESIA - Wawan Fransisco (PROGRESIF: Jurnal Hukum, 2017)
Pancasila is a spiritual principle that includes an atmosphere of kebatinan or legal ideals, so it is a source of value. Norms and rules, both moral and state, and master the basic laws of both written or non-written or Convention. Pancasila is the foundation of the Republic of Indonesia as found in the Preamble of the 1945 Constitution of the Republic of Indonesia, whose birth was forged in the Indonesian national process. Pancasila historically has a legal basis in which Pancasila is the basis or direction in the making of law in Indonesia. Juridically, Pancasila is clearly the law of all sources of law in Indonesia.